2013
DOI: 10.1161/strokeaha.113.003140
|View full text |Cite
|
Sign up to set email alerts
|

Combined 18 F-FDG PET-CT and DCE-MRI to Assess Inflammation and Microvascularization in Atherosclerotic Plaques

Abstract: S troke is the fourth leading cause of death in the UnitedStates and a leading cause of long-term disability. Atherosclerosis is underlying in the majority of clinical cardiovascular events, such as stroke. 1 Inflammation is an important feature of plaque progression and vulnerability.2,3 It can be quantified noninvasively with 18 fluorine-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography/computed tomography (PET-CT) with excellent reproducibility. [4][5][6] Neovascularization is another important fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 15 publications
0
42
0
2
Order By: Relevance
“…13 In contrast, Trujman et al recently reported a positive and significant weak correlation (r s 0.30, P = 0.035) between FDG TBR and mean K trans in 49 patients with carotid stenosis of 30-69% and transient ischemic attack or minor stroke. 14 Furthermore, in 17 patients with suspected supra-aortic arteritis, Cyran et al showed a positive significant strong correlation between mean FDG TBR and DCE-MRI extraction fraction. 26 The discrepancy in correlations may relate to the magnitude of plaque inflammatory activity at the time of noninvasive imaging.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 In contrast, Trujman et al recently reported a positive and significant weak correlation (r s 0.30, P = 0.035) between FDG TBR and mean K trans in 49 patients with carotid stenosis of 30-69% and transient ischemic attack or minor stroke. 14 Furthermore, in 17 patients with suspected supra-aortic arteritis, Cyran et al showed a positive significant strong correlation between mean FDG TBR and DCE-MRI extraction fraction. 26 The discrepancy in correlations may relate to the magnitude of plaque inflammatory activity at the time of noninvasive imaging.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular and pharmacokinetic imaging techniques, such as 2-Deoxy-2-[ 18 F]fluoroglucose (FDG) positron emission tomography/computed tomography (PET/CT) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) allow measurement of metabolic activity 8-10 and neovascularization, 11, 12 respectively. While studies have shown the feasibility of imaging plaques with FDG-PET and DCE-MRI, 13, 14 and some have attempted limited correlation between histological staining and PET 15, 16 or MRI, 12 inconsistent results have emerged, perhaps underscoring that the mere presence of macrophages or microvessels may not reflect the prevailing inflammatory activity. Indeed, mononuclear phagocytes exhibit considerable functional diversity, such that simply enumerating these cells discloses little about their state of inflammatory activation.…”
mentioning
confidence: 99%
“…25 Meanwhile, some studies have investigated the relation between inflammation and angiogenesis using DCE-MRI. 26,27 …”
Section: Introductionmentioning
confidence: 99%
“…Some authors have found a weak correlation between the 2 processes, 20 which is contradicted by others. 21 We could find no correlation between either of these major determinants of plaque vulnerability, highlighting the practical challenges in defining imaging strategies with which to assess plaque vulnerability.…”
Section: Discussionmentioning
confidence: 91%
“…23,24 In previous studies to image vulnerable plaques, multimodality imaging has been investigated. In particular, the combined assessment of inflammation by 18 F-FDG PET-CT and neovascularization by dynamic contrast-enhanced magnetic resonance imaging has been evaluated in patients with carotid plaques, 20,25,26 with divergent results reported (inverse, weak, or a moderate correlation between inflammation and neovascularization). However, systematic histological validation was either lacking in those studies or limited to a comparatively small number of patients.…”
Section: Discussionmentioning
confidence: 99%